Antibacterial Action of Essential Oils of Artemisia as an Ecological Factor: I. Antibacterial Action of the Volatile Oils of Artemisia tridentata and Artemisia nova on Aerobic Bacteria - Nagy, Julius G. (1967)
Bacterial response to increasing amounts of the volatile oils varies significantly according to species of bacteria tested. Among the four species examined, Escherichia coli was the most resistant to the oils, followed by Neisseria sicca, Bacillus subtilis, and Staphylococcus aureus. The oils of Artemisia tridentata seem to have the same degree of antibacterial action as oils obtained from A. nova.